Article Review: Testing for Detection of Low Pig (Porcine) DNA in Cosmetic Products and Health Supplements - Indah Puspita Syafitri, Raden; Fil Ayatil Karimah, Naqiyyah; Ratnawulan Mita, Soraya (Universitas Padjadjaran (Unpad), 2023)
The increase in the Muslim population worldwide has led to rapid growth in the halal product industry. Currently, halal food holds the largest proportion in the global market for halal products, followed by cosmetics and health supplements as one of the main sectors. In the raw materials used for capsule shells and the manufacture of cosmetics, many ingredients come from non-halal sources, such as gelatin, fatty acids, glycerin, and collagen, which are derived from pigs. However, the presence of pork ingredients in cosmetic products and health supplements is prohibited in certain religions, such as Islam. Therefore, the detection of lard in cosmetic and pharmaceutical products plays a crucial role for the benefit of Muslim consumers. Many methods have been developed to detect pork content in highly processed products, one of which is the DNA-based method. This literature review was conducted to explain DNA isolation methods and detection techniques that can be used for pig DNA analysis. A literature search was performed through online databases, and 14 research journals were found that met the inclusion criteria. Based on the collected research, DNA-based methods, including the Polymerase Chain Reaction (PCR) and its modifications, have demonstrated the ability to detect porcine DNA in products like cosmetics and health supplements. The selection of DNA detection and isolation methods depends on the type of sample under examination, thus enhancing the accuracy and success of porcine DNA detection.Keywords: DNA analysis, Pig DNA, Pig Content, Cosmetics, PCR, Health Supplements.